2017
DOI: 10.1136/archdischild-2016-312506
|View full text |Cite
|
Sign up to set email alerts
|

C reactive protein in healthy term newborns during the first 48 hours of life

Abstract: Postnatal age and mode of delivery significantly influence CRP values. Reliable reference values are crucial in order to obtain an adequate diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
(6 reference statements)
5
47
2
1
Order By: Relevance
“…It has previously been suggested that prenatal exposure to meconium may be a cause of increased CRP concentrations . We did not find that meconium stained amniotic fluid affected the neonatal CRP values, possibly since the meconium staining was moderate and the infants had no symptoms of meconium aspiration.…”
Section: Discussioncontrasting
confidence: 64%
“…It has previously been suggested that prenatal exposure to meconium may be a cause of increased CRP concentrations . We did not find that meconium stained amniotic fluid affected the neonatal CRP values, possibly since the meconium staining was moderate and the infants had no symptoms of meconium aspiration.…”
Section: Discussioncontrasting
confidence: 64%
“…CRP is the most extensively studied acute-phase reactant in neonates. It is widely available and its determination is simple, fast, and cost-effective ( 54 , 55 ). The mean CRP level in healthy term infants undergoes a physiological rise from ~1 mg/L at 12 h of age to ~4 mg/L at 48 h of life ( 55 ).…”
Section: Efficient Sepsis Care—basic Elementsmentioning
confidence: 99%
“…31 Specificity values are higher, consistently reported as >90%, even though elevations of CRP can be caused by uninfectious inflammatory processes, such as meconium aspiration and prolonged transition. 32 In both LOS and EOS, accuracy of CRP as a diagnostic marker improves with serial measurements. 31,33 Using CRP in combination with other biomarkers, particularly those that rise early in the course of infection, such as nCD64, IL6, or IL8, has also been shown to be beneficial and can be useful in tracking response to treatment.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%